Measurement of power in research reactors using the neutron noise technique - Gómez, Ángel; Waldman, Ricardo Marcelo; Laggiard, Eduardo (Comisión Nacional de Energía Atómica; Argentina)
Fil: Gómez, Ángel Comisión Nacional de Energía Atómica; Argentina